The relationship between entrepreneurs’ financial literacy and business performance among entrepreneurs of Bauchi State Nigeria - M. Usama, Khadija; Wan Yusoff, Wan Fauziah (African British Journals, 2018)
Financial literacy of entrepreneur has been acknowledged as an important aspect that contribute to the success of any business. Many studies have proven that entrepreneurs who possessed high level of financial literacy contribute to success of their business in term of financial and non-financial success. Despite the important of this aspect there is limited study that explore this issue in Nigeria. Therefore, this study explores the relationship between financial literacy and business performance of entrepreneurs in Bauchi State Nigeria. A survey questionnaire was sent to a random sample 500 entrepreneurs which resulted in 386 useable returned questionnaires. The result revealed a statistically significant relationship between the different dimension of financial literacy and entrepreneurial business performance. Thus, the findings prove that financial literacy plays significant role in improving business performance. Therefore, the entrepreneurs need to improve their financial literacy skill in order to enhance their business performance.